Comparative Analysis on the Board and Academic Performances of BS Criminology Graduates - LP. Guadamor, Maita (International Journal of Psychosocial Rehabilitation, 2020)
The College of Criminal Justice Education of Cagayan State University Piat Campus offering the Criminology Program is mandated to comply with the requirements. The licensure examination results speak of the preparedness of students in taking the examination, the quality of instruction by the faculty and the exposure of the students to practical learning experiences through the equipment and apparatuses provided by the administration. The conduct of this research aimed to make a comparative analysis on the board and academic performances of BS Criminology graduates of 2016 and 2017, CSU Piat, Cagayan. This study used the descriptive normative survey method utilizing documentary analysis as a technique in gathering the required data. Reference.com defines that descriptive-normative survey combines two research methods which involve the gathering of information to describe the object of study as it is, has been or is viewed, which is the descriptive method, and the critiquing of the object to identify ways to improve it, the normative method. The respondents were the graduates from the College of Criminal Justice Education at Cagayan State University Piat Campus in the school years 2015-2016 and 2016-2017. Total enumeration was employed in selecting the 49 respondents who took the Criminologist Licensure Examination (CLE) administered by the Professional Regulation Commission. From the findings of the study, it can be concluded that the general weighted average of graduates in the six subject areas are correlated with the results of the board examination as well as the identified factors attributed to the passing or failing in the board examination and that the researcher strongly recommends that the Faculty members should regularly update their knowledge and competencies along with the subject areas being handled to contribute to the increase passing rate, enforce a stringent screening and retention policies for criminology students as regards grade point average and curriculum enrichment and periodic review of the course contents, in consultation with the subject-experts, should be done.